Pengaruh Mutasi dan Pelatihan Kerja terhadap Semangat Kerja dan Dampaknya pada Prestasi Kerja Pegawai pada Kantor Kementerian Agama Kota Cilegon - Putri Wahyu Novika (COSTING : Journal of Economic, Business and Accounting, 2018)
Job achievement is very important for an organization or company to achieve its goals. The expected goal can be achieved through this research is to see the Effect of Mutation and Job Training on Job spirit And Its Impact at Ministry of Religion Office Of, Cilegon. The sample in this research were 100 employees of Cilegon city ministry office of total population of 339 employees. Data analysis technique used is path analysis. The results show that there is a significant influence between mutation, job training system and job spirit partially. Job mutations (X1) and job training (X2) affect job spirit (Z) by 85 percent, and the rest are influenced by other variables. Furthermore there is also significant influence between work mutation, job training and work morale on job performance partially, where the influence of 78,5 percent, and the rest influenced by other variables Keywords: mutation, job training, morale, employee achievement